Rancangan pelayanan konveksi dengan integrasi metode Service Quality dan Quality Function Deployment (Studi kasus : Bandung Konveksi) - Dermawan, Dedi; Rayendra, Rozar; Ruhil, Zainul; Ardi, Hendri Ali; Jumali, Denur (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Service is one of the important factors that need to be considered for the Industry, Bandung Konveksi is a company that provides various uniforms, such as for schools and offices. The company has experienced a decline in customers and revenue every year due to dissatisfaction with services. This study aims to identify service variables that are less important and need improvement, and to develop improvement proposals based on priorities. The methods used are Service Quality and Quality Function Deployment. The research begins by determining the variables of customer needs, followed by determining the level of customer satisfaction. Then, determine the priority of service quality improvement and end with the preparation of service improvement proposals. The results showed a negative GAP of -2.17 on average, indicating customer dissatisfaction. Importance performance analysis identified 7 important variables that need to be improved. Quality Function Deployment determined 6 improvement priorities: providing training to employees, implementing structured handling procedures using customer relationship management (CRM), improving communication efficiency by utilizing chatbots, optimizing detailed production schedules, being polite and courteous, and establishing procedures for handling the change process.